2014
DOI: 10.1111/jam.12551
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia fergusonii and Escherichia albertii isolated from water

Abstract: Aims: The aim of this study was to characterize Escherichia fergusonii and Escherichia albertii isolated from water. Methods and Results: The characterization of E. fergusonii and E. albertii isolated from water was determined using an Escherichia coli-specific uidA PCR, a tuf PCR, and with phylogenetic analysis using three housekeeping genes (adk, gyrB, and recA) from the E. coli MLST scheme, selected for their ability to discriminate among all Escherichia species. Among the 527 isolates tested, 25 (4Á7%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…We identified different profiles based on rpoB types, but no phenotype was 100% consistent for all isolates. These results agree with those of Maheux et al (20) and were not surprising because the Vitek-2 system has not been optimized to detect E. albertii. E. albertii was initially described as nonmotile, but we identified motile isolates using SIM medium.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We identified different profiles based on rpoB types, but no phenotype was 100% consistent for all isolates. These results agree with those of Maheux et al (20) and were not surprising because the Vitek-2 system has not been optimized to detect E. albertii. E. albertii was initially described as nonmotile, but we identified motile isolates using SIM medium.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that rare sequences of these genes exist in the E. albertii populations that are not detected with the PCR primers used here. Recently, new eae variants of E. albertii isolates have been described by Oh et al (7) and Maheux et al (20). Also, Toth et al found new variants of cdt (18).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Polymerase Chain Reaction (PCR) or MLST based tests for specific genes for identification of Escherichia spp. have been described (Ooka et al, 2013, Maheux et al, 2014, Maheux et al, 2014). A PCR that detects the uidA gene (encoding the b–glucuronidase enzyme) is frequently used to identify E. coli (Bej et al, 1991, (Frahm and Obst, 2003), Pavlovic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%